The Lord’s Song in a Divided Land: the Engaged Music of Brazilian Protestants under Military and Religious Repression (Per Musi, 2017)
This paper examines a selection of socially engaged Protestant songs of the 1970s, when the cultural‐ideological polarization between “alienated” and “engaged” in the sphere of Brazilian popular music reverberated in the realm of Brazilian Christian music. Our goal is to examine the components of musical nationalism and political and social engagement of those Protestant songs, and also to analyze how those songs expressed an idealization of the future, “the days to come” predicted both by secular protest songs and Protestant hymns.